C-erbB3 protein expression in ovarian cancer. Issue 4 (August 1996) - Rajkumar, T; Stamp, G W H; Hughes, C M; Gullick, W J
Abstract : Aims —To study the prevalence of overexpression of c-erbB3 growth factor receptor in ovarian carcinomas and to analyse its relation to histological subtype, stage and grade of the tumours. Methods —Ninety eight ovarian carcinomas were evaluated immunohistochemically using the RTJ1 monoclonal antibody raised against a synthetic peptide, the sequence of which was derived from the cytoplasmic domain of the c-erbB3 protein. Results —Of the tumours, 16% (16/98) overexpressed c-erbB3 protein relative to normal ovarian epithelium, whereas 22% (22/98) were completely negative. There was a statistically significant association between overexpression and well differentiated grade. Conclusions —These findings suggest that c-erbB3 protein overexpression occurs in a significant proportion of ovarian cancers and is correlated with differentiation. Overexpression may merit further investigation as a potential prognostic indicator and as a target for new treatment.